About flowers and cannons: protest songs in popular music festivals (Per Musi, 2014)
The present article discusses some protest songs performed at the “Popular Music Festivals” held between 1965-1969 aiming to understand their role in the social and political context of that era. Based in a phenomenological and dialectic approach, analysis of videos and audio from performances of the selected songs were made, in a Cultural History perspective. Thus, the authors’ reception of the recordings of that period was privileged. We can conclude that there are some convergences between the characteristics of the analyzed songs and also that they functioned as a means of questioning the political situation in a veiled way.